(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
In the past few decades, considerable attention has been focused on the development of new drug delivery system (NDDS). The NDDS should ideally fulfill two prerequisites. Firstly, it should deliver the drug at a rate directed by the needs of the body, over the period of treatment. Secondly, it should channel the active entity to the site of action. Conventional dosage forms including prolonged release dosage forms are unable to meet none of these. At present, no available drug delivery system behaves ideally, but sincere attempts have been made to achieve them through various novel approaches in drug delivery. The aim of present work is to develop a niosomal drug delivery system of aceclofenac. To perform drug-polymer compatibility FT-IR studies were carried out and observed that there was no interaction between the APl and excipients. 8 niosomal formulations are prepared by the thin film hydration method using the cholesterol as the phospholipid. Prepared niosomal formulations were characterized by vesicle size, shape, surface charge, entrapment efficiency, drug content and invitro drug release studies. The vesicle size, size distribution and zeta potential of the optimized formulation (F5) was found to be 65.6 nm and zeta potential was found to be -1.5mV. Size distribution curve confirms the normal size distribution of the vesicles. The % entrapment efficiency of niosomal vesicles formulations were found to be in the range of 54.18±0.59 to 92.71±0.56 and optimized formulation was found to be 92.71±0.56 and drug content of niosomes formulations (F1to F8) were determined to be in the range of 94.6 -97.8%. The pH of all topical niosomal gels were found to be in the range of 7.4±0.02 to 7.4±0.08.The best fit with higher correlation (r2> 0.99) was found with the Zero Order Release and follows Korsemeyer peppas equation for all the formulations, which means that release of Aceclofenac from the lipid bilayer vesicles were due to diffusion. The stability studies were carried out and there was no significant change found in the formulations.